A numerical simulation for determination of velocity encoded MR parameters - Fox, James F.; Doyle, Mark W.; Anayiotos, Andreas (My University, 1996)
Several current investigations aim at developing methods of measuring valvular regurgitation using velocity encoded magnetic resonance (MR) imaging. MR flow encoding provides useful three-dimensional spatial and velocity information. While still in the preliminary stages, these investigations must distinguish the optimum scan parameters necessary to minimize acquisition time and maximize quantitative results. Scan parameters of particular interest are slice thickness and slice orientation. This simulation uses velocity information from computational fluid dynamic (CFD) models to create a numerical, flow dependent, MR scan proximal to an orifice. The purpose of this simulation is to analyze the effect of slice thickness and slice orientation on measuring flow proximal to an orifice. Results indicate that centerline distribution for the four millimeter (mm) slices compare best to the numerical and 1 mm slices, considering that larger slice thicknesses reduce scan time. In addition, given the 4 mm slice thickness, perpendicular slices provide more useful velocity information within the region of interest.
Keywords: Magnetic resonance imaging; Computer simulation; Hemodynamics; Finite element method